Body-mediated energy loss conversion for personalized cell vitalization. (September 2021) - Yong, Hyungseok; Jung, Sungwon; Heo, Deokjae; Choi, Woojin; Chung, Jihoon; Cho, Seongeun; Hwang, Patrick; Song, Hyeonhui; Koh, Won-gun; Lee, Wonhwa; Lee, Sangmin; Hong, Jinkee
Abstract: Unlike chemotherapy, physical stimulation is body-friendly method which does not introduce foreign substances into the human body; however, since the use of the separate power source is dominant, there are forced restrictions. Herein, we report an innovative electrical stimulation method using the body-mediated energy loss conversion (BELC) system. The BELC system is a structure-concept-device that concentrates a local electric field in the desired area by utilizing energy loss from body movement as a power source; and the human body as an energy transfer medium. Concentrated electrical energy in the BELC system induces a low-frequency electric field that vitalizes the cell functions locally. Results from 3D simulation, designed cloth (patch, sleeve, athleisure) containing the BELC system and ex-vivo experiments demonstrate the electric field concentration through the human body without additional electrical components. Vitalization of cells and skins by the BELC system was inspected via in-vitro and in-vivo model; and insignificant side-effects of energy transfer pass-through mouse body were investigated. Graphical Abstract: ga1 Highlights: New electrical stimulation method which can stimulate cells internally and personally via body-mediated was proposed. This study clarified the mechanism of body-mediated energy loss conversion (BELC). Design of cloth-wear with BELC system was proposed to avoid user discomfort. BELC enhanced wound regeneration without damage to organs on its the pathway or immune response.